State and development prospects of dental care for the Ukrainian population - O. V. Voznyi; S. M. Hermanchuk; V. I. Struk; V. I. Bida; A. V. Pohorila (Zaporozhye State Medical University, 2019)
The results of epidemiological studies and statistics of the Ministry of Health of Ukraine show that in recent years, the level of dental morbidity in Ukraine remains high. Late dental care causes such complications as partial and total loss of teeth, aesthetic and functional disorders, and requires dental rehabilitation with the use of complex structures of dentures. Despite the development of dental science and the introduction of modern methods of treatment of dental diseases into practice that allow solving the most difficult clinical situations, the level of dental morbidity remains high. The decrease in the level of dental health negatively affects the state of general somatic health, causing social maladaptation, which in general is negatively reflected at the level of country's socio-economic development. The article presents quantitative and qualitative indicators of dental care to the population of Ukraine in recent years in the dynamics, which testify to the need for constant monitoring of the state of dental health of the population, the introduction of new therapeutic diagnostic and medical-preventive technologies and the necessary forms of statistical reporting, which will facilitate the creation of effective systems for assessing the quality and effectiveness of dental care and raising the level of dental health of the population. Aim. The aim of our study is to assess the status and prospects of dental care for population by comparative analysis of changes in providing orthopedic care for the Ukrainian population by government institutions, according to dynamic statistics of Ministry of Health of Ukraine. Materials and methods. For the analysis, selected data of scientific literature, statistical indicators of the Ministry of Health of Ukraine and the Center of Medical Statistics of the Ministry of Health of Ukraine were used. Conclusions. The results of the analysis showed the existence of changes in the quantitative indicators of dentures both in years and regions. Coordination of dental care and the introduction of an effective system of monitoring will contribute to the creation of an effective system for assessing the quality of dental care.